Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Karyawan Pada PT Snapindo Warlab Sukses Tebet - Farah Alya Nadilah; Rani Rani; Purwatiningsih Purwatiningsih (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
The purpose of conducting this research was to find out whether there is an influence of workload and work stress on employee performance at PT Snapindo Warlab Sukses Tebet. Workload and work stress are issues that need to be considered by companies because they can reduce employee performance. In this study the authors used quantitative methods, using primary and secondary data sources. The sample in this research is a number of 36 respondents. Data collection techniques through observation, questionnaires and literature study. The analytical method used in this study used the multiple regression analysis method and to process the data using SPSS version 26. The results in this study stated that: 1) Workload has a partial positive and significant effect on employee performance at PT Snapindo Warlab Sukses Tebet 2) Work stress has a negative and partially significant effect on employee performance at PT Snapindo Warlab Sukses Tebet 3) Workload and work stress have a positive and significant effect simultaneously on employee performance at PT Snapindo Warlab Sukses Tebet.